Pengaruh Media Video PembelajaranTerhadap Kemampuan Pemahaman Konsep Siswa - Vitaloka, Velya; Yusup Efendi, Akhmad; Saputra, Herizal (Yayasan Darussalam Bengkulu, 2020)
The purpose of this study was to determine whether or not there is an effect of video learning media on students' conceptual understanding abilities. This research is a quantitative study using experimental methods. In this study, a pre-experimental design was used using one group pretest-posttest design in order to determine the effect of learning video media on students' conceptual understanding abilities. The subjects of this study were 21 students of class XI IPA at Madrasah AliyahDarulQalamMerigiKelindang. In this research, there are several preparations which are divided into the preparation stage, the implementation stage and the analysis stage. Data collection techniques using essay form tests. The purpose of the test is to determine the ability of students to understand concepts after being given learning video media, the researcher analyzes the data using the SPSS application. So from the results of the study it can be concluded that there is a significant influence in the learning process using video learning media on the students' concept understanding ability in class XI IPA Madrasah AliyahDarulQalamMerigiKelindang.